Evaluation of the antimicrobial performance of menthol and menthol-based deep eutectic solvents as potential future antibiotic - Azmi, Nor Azrini Nadiha; Elgharbawy, Amal A.M.; Mohd Salleh, Hamzah; Hayyan, Adeeb (EDP Sciences, 2021)
Triggered by the strong antimicrobial activities of menthol and various fatty acids, eutectic mixtures based on the components are developed, producing new solvents that have possibilities to become a new antibiotic. This study aims to provide an insight into the antimicrobial activities of the new deep eutectic solvents (DESs) developed. Menthol-based DES combined with fatty acids, namely propionic acid, butanoic acid, hexanoic acid, octanoic acid, decanoic acid, and levulinic acid, were successfully obtained and their thermal profile was analyzed. The antimicrobial potential of DES systems was evaluated against both Gram positive and Gram negative bacteria. Owing to the activities of the start-up components, the results are considered promising, and this illustrates the potential of the newly obtained DESs as a new antimicrobial agent in various fields such as food, cosmetics as well as pharmaceutical